Aradus brevicollis Fallén, ein interessantes Tier der deutschen Fauna nebst einigen Bemerkungen über das Integument der Aradiden (Heteroptera: Aradidae). - Jordan, Carl Hermann Christian (Contributions to Entomology = Beiträge zur Entomologie, 1957)
There is given a report on the occurence of the North European-Siberian species Aradus brevicollis Fall, in Saxony (Upper Lusatia), and a description of the second, fourth, and fifth larval instar. By means of histologic examination there are rendered globe-shaped organs of sense (tangoreceptive function). Spots close by without organs of sense, present in all Aradidae, are provisionally called "maculae". More than 100 of them are frequently present. On account of the fact that near to the pleurites muscles are ordinary recognitable and the chitine sheets of the integument are enlarged within the range of the "maculae", the author supposes these "maculae" being conducive to the statics of abdomen.